Irreversible Electroporation: An Emerging Immunomodulatory Therapy on Solid Tumors - Zhang, Nana; Li, Zhuoqun; Han, Xuan; Zhu, Ziyu; Li, Zhujun; Zhao, Yan; Liu, Zhijun; Lv, Yi (Frontiers in Immunology, 2022)
Irreversible electroporation (IRE), a novel non-thermal ablation technique, is utilized to ablate the unresectable solid tumors and demonstrates favorable safety and efficacy in clinic. IRE applies electric pulses to alter the cell transmembrane voltage, and causes nanometer-sized membrane defects or pores in the cells, which leads to loss of cell homeostasis and ultimately results in cell death. The major drawback of IRE is the incomplete ablation and the susceptibility to recurrence, which limits its clinical application. Recent studies have shown that IRE promotes the massive release of intracellular concealed tumor antigens that become an "in situ tumor vaccine", inducing a potential anti-tumor immune response to kill residual tumor cells after ablation and inhibit the local recurrence and distant metastasis. Therefore, IRE can be regarded as a potential immunomodulatory therapy, combined with immunotherapy will exhibit synergistic treatment effects on malignant tumor, which provides a broad application prospect for tumor treatment. This work reviewed the current status of clinical efficacy of IRE on tumor treatment, summarized the characteristics of local and systemic immune response induced by IRE in tumor-bearing organisms, and analyzed the specific mechanisms of the IRE-induced immune response. Moreover, we traced the current research progress of IRE combined with immunotherapy in the treatment of solid tumors. Based on these, we put forward the deficiencies of current preclinical researches on animal models and analyzed the possible reasons and solutions. And we also proposed the possible demands for clinical researches. This review aimed at providing a theoretical and practical guidance for the combination of IRE with immunotherapy in the treatment of malignant tumors.